Novel antibodies reacting with two neighboring gangliosides are induced in rabbits immunized with bovine brain gangliosides - Moyano, Ana L. (2012)
Immunization of rabbits with bovine brain gangliosides induced an experimental neuropathy, with clinical signs resembling Guillain-Barré syndrome. All the immunized animals developed immunoglobulin G immunoreactivity to GM1 ganglioside. In a few (4 of 27) animals, an additional anti-ganglioside antibody population showing an unusual binding behavior was detected. Enzyme-linked immunosorbent assay and thin-layer chromatography immunostaining analyses showed that the binding of these unusual antibodies required the presence of two co-localized gangliosides. Maximal interaction was observed to a mixture of GM1 and GD1b, but the antibodies also showed density-dependent binding to GD1b. The antibodies were purified by affinity chromatography and displayed the ability to target antigens in biological membranes (rat synaptosomes).